VAPSHE ARA: ATTITUDES OF ENGLISH PHILOLOGY STUDENTS IN GEORGIA TOWARDS THE RUSSIAN LANGUAGE - Mitaishvili-Rayyis, Yasmine (Online Journal of Humanities ETAGTSU, 2023)
This article explores the beliefs and attitudes of English Philology students in Georgia towards the Russian language, focusing on Russia’s linguistic prestige and history within Georgia, and the current state of Russian-Georgian relations. The study employs a qualitative research approach through interviews and contrastive analysis to investigate linguistic prestige, models for language context, relevant educational and language policy, and student perspectives. This exploration is rooted in sociolinguists, though draws from linguistic anthropology, and political science, taking an interdisciplinary approach to the subject. The study seeks to answer various research questions, including the role of Russian in contemporary and historical Georgia, the factors that influence the students' perceptions of the Russian language, and how historical context shapes linguistic attitudes. The findings suggest that the status of Russian in Georgia reflects the country’s historical, cultural, and political context, where the promotion of both Georgian national identity and language, as well as the English language, has led to the marginalization of Russian in most domains. Additionally, the research underscores the significant role of the legacy of the Soviet occupation in shaping the views of English Philology students toward the Russian language. Overall, this article sheds light on the complex relationship between language, politics, and identity in contemporary Georgia. Full Text (PDF)